2017
DOI: 10.13004/kjnt.2017.13.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Kümmell's Disease Treated with Percutaneous Vertebroplasty: Minimum 1 Year Follow-Up

Abstract: ObjectiveTo evaluate the radiographic and clinical outcomes of percutaneous vertebroplasty (PVP) in patients with Kümmell's disease.MethodsA retrospective review was conducted for 19 vertebrae in 18 patients, between January 2012 and June 2016. A visual analogue scale (VAS) score was used to determine each patient's subjective level of pain (0=no pain to 10=severe pain) preoperative, immediately postoperative and at the last follow-up (at least 12 months after PVP).Radiographic parameters such as regional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and at the same time partially restore the height of the vertebra and correct the kyphosis [11,[21][22][23][24][25][26][27][28]. During spinal flexion and extension, due to the presence of IVC and the formation of false joints, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…After filling the fissures in the vertebral body with bone cement, the height and kyphosis deformity of the vertebral body were partially restored and corrected, and the abnormal activity of the injuried vertebral body was eliminated, which was an important reason for pain relief [11]. Previous studies have found that both PVP and PKP can effectively relieve the lower back pain of Kümmell's disease, achieve satisfactory clinical effect, and partially restore the height of the vertebra and correct the kyphosis [11,[22][23][24][25][26][27][28][29]. During spinal flexion and extension, due to the presence of IVC and the formation of pseudojoint, the injured vertebra of Kümmell's disease can stretch and expand, which can widen the fractured vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…After the ssures of the fractured vertebral body lled with bone cement, the abnormal activity of the vertebral body was eliminated and the fractured vertebrae was stabilized, which was an important reason for pain relief [16]. Besides, the height of the vertebral body was partially restored and kyphosis deformity was partially corrected [16][17][18][19][20][21][22][23][24]. The ODI and VAS after PVP surgery both in Kümmell's disease and OVCFs groups were signi cantly decreased, but the mean scores were higher in the Kümmell's disease group than in the OVCFs groups [25].…”
Section: Resultsmentioning
confidence: 99%
“…Kümmell's disease is a chronic, non-healing osteoporotic vertebral compression fractures (OVCFs), which is associated with the ischemic necrosis of vertebral body after fracture and vertebral pseudarthrosis [1,2]. Due to the continuous collapse of vertebral body after minor trauma, clinical manifestations are often intractable low back pain, and even the symptoms of spinal nerve function damage [3]. Thoracolumbar vertebrae is the most common site of its occurrence.…”
Section: Introductionmentioning
confidence: 99%